2017
DOI: 10.1098/rsob.170101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture and regulatory impact on hepatic microRNA expression linked to immune and metabolic traits

Abstract: Regulation of microRNA (miRNA) expression contributes to a wide range of target gene expression and phenotypes. The miRNA expression in the liver, the central metabolic organ, was examined in 209 pigs, and integrated with haematological and clinical biomarkers of metabolic and overall health, mRNA-target expression levels and single-nucleotide polymorphism (SNP) genotypes. The expression levels of 426 miRNA species correlated with plasma haematological or biochemical traits (r² = |0.19–0.45|, false discovery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
4
10
0
2
Order By: Relevance
“…Five miRNAs of the let-7 family belong to the molecular panel for PU. Previous studies found that the expression of the let-7 family correlated significantly with glucose levels and regulates glucose metabolism [55,56]. IGSF10 was negatively correlated and predicted as a target of miR-148a-3p and miR-142a-5p in this study.…”
Section: Discussionsupporting
confidence: 64%
“…Five miRNAs of the let-7 family belong to the molecular panel for PU. Previous studies found that the expression of the let-7 family correlated significantly with glucose levels and regulates glucose metabolism [55,56]. IGSF10 was negatively correlated and predicted as a target of miR-148a-3p and miR-142a-5p in this study.…”
Section: Discussionsupporting
confidence: 64%
“…In addition to their role in cocaine-induced neuroplasticity, both miRNAs were predicted to target genes implicated with metabolic processes, with a more pronounced list of hits associated with miR-181 functioning (25%). Previous studies have suggested a role for miR-124 and miR-181 on the regulation of metabolic traits in fat tissues and in the liver (Pan, Jing, Qiao et al, 2018;Ponsuksili, Trakooljul, Hadlich et al, 2017). Interestingly, the systemic pathophysiology of CUD includes several metabolic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In a marker regression analysis, expression is regressed onto the genotype. To be consistent with the literature [14, 16, 20] and the controlled nature of recombinant inbred mice (all of which are male), no covariates were included in the model. 95% Bayes’ credible intervals were also calculated using R/qtl.…”
Section: Methodsmentioning
confidence: 99%